MODEL OPTIMASI ECONOMIC PRODUCTION QUANTITY DENGAN SISTEM DELIVERY ORDER - Puspita, Nikken Prima; Khabibah, Siti; Ratnasari, Lucia (MATEMATIKA, 2014)
The aims of Economic Production Quantity models are for manage the production schedule and product inventory. The first Economic Production Quantity model developed by E.W Taft on 1918. Taft make some asumption such as daily demand rate constant, daily production rate constant, not stockout allowed, single item product and daily production rate are more than daily demand rate. On the process of delivery product, Â there is not transportation cost. Pasandideh dan Niaki on 2010 was constructed an Economic Production Quantity models with discrete delivery order. In this research we discussed the Economic Production Quantity model which products delivered by multiple palet system and with transportation cost.